Consequence assessment of nuclear-powered vessel accidents and floating nuclear power plant transit accidents in the Arctic region - Voutilainen, Mikko; Peltonen, Tuomas; Mattila, Aleksi; Tanskanen, Aapo (Säteilyturvakeskus, 2023)
Radiological consequence assessment of atmospheric releases of radioactive materials due to accidents on Nuclear-Powered Vessel (NPV) and during a transit of Floating Nuclear Power Plant (FNPP) were performed. The assessment was performed using a probabilistic approach for open sea locations in the Gulf of Finland and near the Norwegian coast in the Barents Sea, and coastal locations nearby the city of Tromsø and the Kara Strait on the Northern Sea Route. The dose rates and radiation doses to emergency workers and people close to the accident site were estimated, and needed protective actions were evaluated. The decision support system JRODOS was used to model the dispersion and deposition of radioactive substances in atmospheric release and to estimate dose rates and the doses to people and emergency workers. The modelling applied previously published radionuclide inventories and release fractions, and NOMADS weather data from the year 2021. The results showed that for the NPV accidents, external dose rate of 100 μSv/h, effective dose of 100 mSv, and thyroid equivalent dose of 100 mSv are exceeded nearby the accident locations. Thus, in case there is habitation in the vicinity of the scene, different protective actions are needed downwind from the accident location to protect people. It was estimated that the recommendation to limit being outside is needed up to 10 km, sheltering indoors up to 3 km and evacuation up to 2 km. Furthermore, the iodine prophylaxis for adults may be needed up to 5 km, and rough estimate revealed that iodine prophylaxis for children and pregnant females is needed up to 10 km. Based on the analyses, emergency workers should wear Personal Protective Equipment (PPE) up to about 5 km from the accident site due to the elevated external dose rates. Furthermore, the emergency workers should take iodine prophylaxis if the air contains radioactive iodine, working hours should be recorded, and alarming external dose rate meters and dosimeters should be used. In prolonged situations, the shift ...